Monitoring of alien mosquitoes in Western Austria (Tyrol, Austria, 2018). - Hans-Peter Fuehrer; Ellen Schoener; Stefanie Weiler; Bita Shahi Barogh; Carina Zittra; Gernot Walder (Public Library of Science (PLoS), 2020)
Mosquitoes are of major importance to human and animal health due to their ability to transmit various pathogens. In Europe the role of mosquitoes in public health has increased with the introduction of alien Aedes mosquitoes such as the Asian tiger mosquito, Aedes albopictus; the Asian bush mosquito, Ae. japonicus; and Ae. koreicus. In Austria, Ae. japonicus has established populations in various regions of the country. Aedes albopictus is not known to overwinter in Austria, although isolated findings of eggs and adult female mosquitoes have been previously reported, especially in Tyrol. Aedes koreicus had not so far been found in Austria. Within the framework of an alien mosquito surveillance program in the Austrian province of Tyrol, ovitraps were set up weekly from May to October, 2018, at 67 sites- 17 in East Tyrol and 50 in North Tyrol. Sampling was performed at highways and at urban and rural areas. DNA obtained from mosquito eggs was barcoded using molecular techniques and sequences were analysed to species level. Eggs of alien Aedes species were found at 18 out of 67 sites (27%). Both Ae. albopictus and Ae. japonicus were documented at highways and urban areas in both East and North Tyrol. Aedes koreicus was found in East Tyrol. During this mosquito surveillance program, eggs of Ae. albopictus, Ae. japonicus, and Ae. koreicus were documented in the Austrian province of Tyrol. These findings not only show highways to be points of entry, but also point to possible establishment processes of Ae. japonicus in Tyrol. Moreover, Ae. koreicus was documented in Austria for the first time.